2013
DOI: 10.5041/rmmj.10129
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System, Cannabinoids, and Pain

Abstract: The endocannabinoid system is involved in a host of homeostatic and physiologic functions, including modulation of pain and inflammation. The specific roles of currently identified endocannabinoids that act as ligands at endogenous cannabinoid receptors within the central nervous system (primarily but not exclusively CB1 receptors) and in the periphery (primarily but not exclusively CB2 receptors) are only partially elucidated, but they do exert an influence on nociception. Exogenous plant-based cannabinoids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 111 publications
1
86
0
4
Order By: Relevance
“…Further studies focusing on chronic stress and CNR1 in zebrafish seem warranted. Studies on mammals have also shown that CB1 is associated with pain and pain perception, where activation of CB1 reduces pain sensitivity (Fine and Rosenfeld, 2013;Guindon and Hohmann, 2009;Wilson and Nicoll, 2002). Higher levels of CNR1 could contribute to poorer inhibitory avoidance learning as the paradigm is based on a potentially noxious stimulus (i.e.…”
Section: Research Articlementioning
confidence: 99%
“…Further studies focusing on chronic stress and CNR1 in zebrafish seem warranted. Studies on mammals have also shown that CB1 is associated with pain and pain perception, where activation of CB1 reduces pain sensitivity (Fine and Rosenfeld, 2013;Guindon and Hohmann, 2009;Wilson and Nicoll, 2002). Higher levels of CNR1 could contribute to poorer inhibitory avoidance learning as the paradigm is based on a potentially noxious stimulus (i.e.…”
Section: Research Articlementioning
confidence: 99%
“…Trends toward improvements with THC:CBD oromucosal spray in patients with 1 or 2 failed prior therapy attempts were broadly similar to those in the ITT population and, occasionally, were even more pronounced, such as the significant improvement in the SF-36 domain of 'bodily pain' in patients in Group 1 which might be explained by the analgesic effect of THC:CBD [17][18][19] . The lack of statistical significance for this same quality of life measure in patients in Group 2 likely reflects the smaller sample size as the same trend was evident.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis has an inhibitory effect via augmentation of gamma-amino-butyric acid (GABA) pathways in the central nervous system (131–133). This produces motor neuron inhibition at spinal levels in mice.…”
Section: Types Of Cam That Pals Commonly Ask Aboutmentioning
confidence: 99%